ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTERNAL DALAM PEMBERIAN KREDIT PADA KOPERASI PEGAWAI REPUBLIK INDONESIA “GURU” SUMBERMANJING WETAN - Hendri Kurniawan; Moh. Amin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The accounting information system and the internal control system are a unity that is equally binding into two inseparable parts. Therefore, accounting information systems and internal control systems are two things that are needed and important, especially in financial institutions for the process of implementing credit. An accounting information system and internal control system can support company activities to run more effectively and efficiently. In financial institutions, the use of credit is not as expected, there are many problems that must be corrected, one of which is often non-performing loans, namely bad loans. The purpose of the research that is expected by the researcher is to find out regarding the application of accounting information systems and internal control systems in the employee cooperatives of the Republic of Indonesia "guru" Sumbermanjing Wetan and whether the application of accounting information systems and internal control systems is effective enough to avoid risks in granting credit. at the Indonesian republican employee cooperative "guru" Sumbermanjing wetan. This research uses a descriptive method. Descriptive method is a research method that seeks to solve problems or answer various questions from the problems being faced. The results of this study The decision making process of credit requests is not adequate. This can be seen from the analysis process at the time of making credit decisions that are not appropriate according to what was informed by one of the informants obtained at the cooperative. If the credit analysis process and credit decisions are not adequate, it will allow the emergence of bad loans.Keywords: Accounting Information System, Internal Control, Credit, Cooperative